De Kaapsche Kerk, the British Empire, slavery, and the discourses of good and evil - Müller, Retief (Stellenbosch Theological Journal, 2024)
It is a well-known history that the Dutch church in South Africa’s Cape colony up until the early 19th century had readily accommodated the institution of slavery as commonly practiced within Cape Dutch society. Slavery was not seen as “good” but generally accepted as an unfortunate reality of life. Some groups of people, particularly those of non-European heritage, were seen within this colonist society as naturally predisposed for slavery. Biblical arguments regarding examples of the non-denunciation of slavery in both Old and New Testament scriptures could easily be mustered in defence of the institution against the rare voices protesting the practice. In that sense the Cape Church was not any different from most other Christian churches in colonial societies worldwide. Yet the Cape church also had some strong antislavery statements and advocates from within its ranks since at least the first half of the nineteenth century. As seen for example in Dreyer’s collection of documents under the title, “Die Kaapse Kerk en die Groot Trek”, several high placed church leaders opposed the migration of Dutch farmers from the Cape colony in the 1830s on the basis that the migration occurred in disobedience to British colonial legislation that were effectively seen as seeking to stamp out slavery and associated practices. The Dutch farmers tended to see the British Empire as an evil empire. The Cape Church leadership, to the contrary, which by then included a number of abolitionist Scottish pastors in its ranks viewed their emigrating members, at least initially, as being in rebellion not only against the civil rulers but also against the church, and they, albeit for the most part unsuccessfully, sought to dissuade the emigrants from abandoning their chosen paths. In the subsequent decades a number of Cape Church pastors sought contact with the migrants with the intent of bringing them back into the fold. This article presents the case of a noteworthy equalisation campaigner in this regard, Rev. D.P.M. Huet. Another episode occurred later in the 19th century in the mission fields associated with the Cape Church in central Africa, Nyasaland as it was known at the time. Again, it is a well-known story that some of the early Christian missionaries in these areas, most notably David Livingstone, confronted slave traders and agitated against the practice which was still rife throughout the region during much of the 19th century. Yet, as far as the Cape Church and Afrikaners more generally were concerned, historical accounts often suggest that particularly the northern Boers were more often themselves involved in the slave trade rather than acting against it. Yet, as this article will indicate the early missionary enterprise of the Cape Church in central Africa actively engaged in anti-slavery activities with a central character in this being missionary, William Hoppe Murray who served as leader of the mission in Nyasaland for a substantial period. The article finally discusses the case of De Kaapsche Kerk (the Dutch Reformed Church in the Cape Colony) in relation to slavery and empire with reference to notions of good and evil.